STUDI LITERATUR: PERANAN SELF REPORTED PADA MASYARAKAT DALAM PENCEGAHAN COVID 19 - Rohman, Fahrul; Nugroho, Setiyo Adi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Self Reported very rarely considered as intervention resolve Pandemic COVID 19 in Indonesia. A literature study was conducted to serve as a reference for the importance of self-reporting in overcoming this pandemic. This literature study uses an electronic database through national and international journals such as science directx, elsiver, NEJM, Google scholar. Inclusion criteria used by the author is to limit or journal article that appeared in the last two years starting in 2019 until 2021. The keyword used for the search was Self reported COVID 19. The results of the Literature Review of 29 journals (Google Scholar 8 articles, science directx 6 articles, Elsiver 7 articles, NEJM 8 articles) 17 published journals did not match the topic of discussion. There were 11 articles that met the criteria and were selected to be used as case studies. The results of the research as a whole show that self-reported is able to provide an overview of COVID 19 in the community and make it easier to find out people with COVID 19.